Ultra-high-speed DNA fragment separations using microfabricated capillary array electrophoresis chips. - Woolley, A T (1994)
Capillary electrophoresis arrays have been fabricated on planar glass substrates by photolithographic masking and chemical etching techniques. The photolithographically defined channel patterns were etched in a glass substrate, and then capillaries were formed by thermally bonding the etched substrate to a second glass slide. High-resolution electrophoretic separations of phi X174 Hae III DNA restriction fragments have been performed with these chips using a hydroxyethyl cellulose sieving matrix in the channels. DNA fragments were fluorescently labeled with dye in the running buffer and detected with a laser-excited, confocal fluorescence system. The effects of variations in the electric field, procedures for injection, and sizes of separation and injection channels (ranging from 30 to 120 microns) have been explored. By use of channels with an effective length of only 3.5 cm, separations of phi X174 Hae II DNA fragments from approximately 70 to 1000 bp are complete in only 120 sec. We have also demonstrated high-speed sizing of PCR-amplified HLA-DQ alpha alleles. This work establishes methods for high-speed, high-throughput DNA separations on capillary array electrophoresis chips.